CA4BPS: an end-to-end context-based approach for business process socialisation. (18th July 2019) - Yahya, Fadwa; Boukadi, Khouloud; Maamar, Zakaria; Ben-Abdallah, Hanêne
Today's enterprises are in quest of innovative ways that would help them demystify the social relations that would exist between them and their stakeholders. To this end, these enterprises have been looking into integrating Web 2.0 into their business processes (BP) to develop social business processes (SBP). Evidently, an enterprise cannot socialise its entire BPs for reasons related to security and feasibility (e.g., technical and financial). This paper proposes an end-to-end approach to assist enterprises in socialising BPs. The approach builds upon enterprise architecture to define contextual elements that would guide the socialisation exercise. It uses analytic hierarchical process to assess the eligibility of BPs to socialisation based on these elements. It also embraces model-driven architecture to model and implement the socialised BPs. The preliminary evaluation of the approach shows encouraging results.